Patient satisfaction, e-health and the evolution of the patient–general practitioner relationship: Evidence from an Italian survey. Issue 11 (November 2016) - De Rosis, Sabina; Barsanti, Sara
Highlights: The e-health user is mainly young, healthy and literate, showing a digital divide in the opportunities of health promotion through the ICT. Internet use for health purposes is affected by experience and satisfaction with the healthcare system, but not with the GPs. Being satisfied with GPs' involvement in decision-making is a key factor affecting the patient behaviour of sharing e-health findings with the GP. In the patient–web–physician triangulation, GPs play an important role in improving the 'appropriateness' of the Internet use. Abstract: Background: Scientific and public interest in the use of the Internet for health-related purposes has grown considerably. Concerns regarding its impact on patient–doctor relationship and risks for patients have inflamed the debate. Literature provides scarce evidence in this field. This paper investigates whether a patient's decision to use the web also depends on previous experience and satisfaction with healthcare. Method: Statistical analyses were conducted using data from a survey of more than 1700 citizens in Tuscany (Italy). The Andersen behavioural model was adopted as framework for investigating two patient behaviours: Internet use for health-related purposes; discussion of online findings with the physician. Two separate multivariate logistic models were performed to verify whether satisfaction and experience with healthcare system and general practitioners were associated with the e-health behaviours. Results: Age, education and dissatisfaction with the healthcare system are the main determinant factors of e-health use. The behaviour of sharing the e-health experience with general practitioners is more diffused among those patients who are more satisfied with physicians for the involvement in the decision-making process and suggestions on life-style. Implications: Whether patients choice to share information found online with the doctor depends on the ability of the doctor to engage patients in decision-making, e-health can produce a 'double-empowerment' process: experienced by the patient on the Internet, and legitimated by the doctor during encounters.